Drug regulatory decision-making: Evidence and real-world data as allies of randomized controlled trials - Santos, Delba Fonseca (Seven Editora, 2023)
With the Covid-19 pandemic, the world has been faced with the pragmatic search for effective treatment and highlighted the importance of real-world evidence and data as valuable for decision-making by different stakeholders. This evidence has brought new insights into efficacy, safety, and quality of drugs with patient-centered clinical outcomes. This paper describes some important elements of real-world evidence and data: 1) they are related to the patient's health status and/or the provision of health care routinely collected from various sources; 2) although, controlled clinical trial results are the basis for clinical decision-making, they can currently incorporate real-world evidence and data; 3) there is increasing use to support regulatory decision-making; 4) are underutilized sources to assess the impact on public health in risk minimization, health technology assessment, costs, and clinical decisions.DOI:https://doi.org/10.56238/globalhealthprespesc-052